Bacterial Spectrum and Antibiotic Resistance Patterns of Ocular Infection: Differences between External and Intraocular Diseases. (21st October 2015) - Wang, Nan; Yang, Qian; Tan, Yiwei; Lin, Liping; Huang, Qiang; Wu, Kaili
Abstract : This study aimed to compare the differences of microbial spectrum and antibiotic resistance patterns between external and intraocular bacterial infections in an eye hospital in South China. A total of 737 bacteria isolates from suspected ocular infections were included in this retrospective study covering the period 2010–2013. The organisms cultured from the ocular surface (cornea, conjunctiva) accounted for the majority of the isolates (82.77%, n = 610), followed by the intraocular (aqueous humor, vitreous fluid), which accounted for 17.23% ( n = 127). The top three species accounting for the external ocular infections were S. epidermidis (35.25%), P. aeruginosa (8.03%), and S. simulans (4.43%). The top three species for the intraocular infections were S. epidermidis (14.96%), S. hominis (8.66%), and B. subtilis (7.87%). The bacteria from the external ocular surface were more sensitive to neomycin, while those from the intraocular specimens were more sensitive to levofloxacin ( P < 0.01). Multidrug resistance was found in 89 bacteria (12.08%), including isolates from both external (13.28%) and intraocular samples (6.30%). The results of this study indicate that the bacteria spectrum of external and intraocular infections is variable in the setting. A high percentage of bacterial organisms were found to be primarily susceptible to neomycin for external infection and levofloxacin for intraocular infection.